A novel archosauromorph from Antarctica and an updated review of a high-latitude vertebrate assemblage in the wake of the end-Permian mass extinction. Issue 6 (2nd November 2018) - Peecook, Brandon R.; Smith, Roger M. H.; Sidor, Christian A.
Abstract: Triassic-aged fossil vertebrates have been sporadically collected from the Fremouw Formation, central Transantarctic Mountains, since their initial discovery in the late 1960s, giving paleontologists insight into high-latitude faunas in the wake of the end-Permian mass extinction event. On a recent expedition (2010–2011), a small reptile skeleton was collected from Graphite Peak, which we present here alongside novel geological data and interpretations taken on site. Antarctanax shackletoni, gen. et sp. nov., is known from a partial postcranial skeleton including cervical and dorsal vertebrae, a humerus, and both pedes. Important morphological information includes well-defined laminae and deep fossae on cervicodorsal vertebrae. The new taxon can be differentiated from previously known Fremouw Formation reptiles (e.g., Prolacerta, Procolophon ), as well as those from the Karoo Basin, South Africa (e.g., Mesosuchus, Proterosuchus, Euparkeria ). Our inclusion of A. shackletoni in phylogenetic analyses of early amniotes finds it as an archosauriform archosauromorph, increasing known archosauriform diversity in the Early Triassic. The fauna of the lower Fremouw Formation traditionally has been considered to represent a subset of the Lystrosaurus Assemblage Zone of the Karoo Basin, with differences largely a result of pronounced differences in sampling intensity. However, a review of recent changes to the fauna, as well as a reassessment of occurrences based on older literature, indicates that significant discrepancies, including the co-occurrences of taxa known from both earlier and later in time and the presence of endemic forms in Antarctica, exist between the faunas of the Lystrosaurus Assemblage Zone and lower Fremouw Formation. http://zoobank.org/urn:lsid:zoobank.org:pub:B1DAD1A4-7054-454D-89B2-17CAF2865AD4 SUPPLEMENTAL DATA—Supplemental materials are available for this article for free at www.tandfonline.com/UJVP Citation for this article: Peecook, B. R., R. M. H. Smith, and Christian A. Sidor. 2019. A novel archosauromorph from Antarctica and an updated review of a high-latitude vertebrate assemblage in the wake of the end-Permian mass extinction. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2018.1536664 .